The Influence of Organizational Culture on Motivation Management - Ciprian GRIGORESCU; Gheorghe Adrian ZUGRAVU (Communications of International Proceedings, 2023)
Culture represents the totality of material and spiritual values acquired by a people and transmitted from generation to generation. In general terms, the impact of culture on management is reflected by people's beliefs and behavior. Conceptually, the notion of interculturality belongs to the last decades and appeared as a natural consequence of the new world trends of universalism and globalization. As a phenomenon, however, interculturality is not new, it has manifested itself in the course of history every time the expansion of a great empire brought together several peoples, several mentalities and several cultures. In this study, I started from the notions of "culture" and "interculturality", going through the influence of culture on management in general, but also on motivational aspects. In this paper, I tried to capture some of the major aspects of cultural influences on motivation management. The development of this study contributes to increasing manager’s awareness of the similarities and differences between managerial approaches used by managers.
Keywords: Culture; Motivation; Management; Organizational Behaviors